2018
DOI: 10.1111/ap.12354
|View full text |Cite
|
Sign up to set email alerts
|

Psychologists’ Application of Clinical Guidelines and Recommended Protocols and Procedures within State Insurance Regulatory Authority Insurance Frameworks: Outcomes for Injured Patients with Musculoskeletal Injuries

Abstract: Objective: In 2010, the State Insurance Regulatory Authority (SIRA), which governs the regulatory functions of workers' compensation insurance (WCI) and compulsory third-party insurance (CTP) within NSW, implemented evidence-based clinical guidelines to improve psychologists' practice. The aims of this study were to determine (a) whether this initiative has reduced claims costs and improved injured patient outcomes and (b) whether it has resulted in psychologists using evidence-based practice. Method: The firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 36 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…The current study adopted a partnership approach with field experts and psychologists to generate recommendations in order to increase adherence with EBP treatment guidelines within the SIRA compensation schemes (Haider et al, ; Tasca, ). Active involvement of psychologists in proposing and examining the feasibility of the recommendations was aimed at improving EBP and increasing engagement to facilitate adoption of the guidelines in ordinary clinical settings (Baker et al, ; Francke, Smit, de Veer, & Mistiaen, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study adopted a partnership approach with field experts and psychologists to generate recommendations in order to increase adherence with EBP treatment guidelines within the SIRA compensation schemes (Haider et al, ; Tasca, ). Active involvement of psychologists in proposing and examining the feasibility of the recommendations was aimed at improving EBP and increasing engagement to facilitate adoption of the guidelines in ordinary clinical settings (Baker et al, ; Francke, Smit, de Veer, & Mistiaen, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that poor injured person outcomes were observed when psychologist's adherence to the treatment principles was low (Haider et al, ). Overall, the study found that psychologists' adherence with the treatment principles contained in the Clinical Framework for the Delivery of Health Services was suboptimal (Haider et al, ). The finding is consistent with research in the mental health field which has found that clinicians lack of trust in EBP stems from their belief that clinical guidelines support the interests of administrators and not patients (Corrigan, McCracken, & Blaser, ; Milne, Gorenski, Westerman, Leek, & Keegan, ).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The role of psychologists within this intervention framework is significant, as the central focus is on the injured person experiencing the pain and includes appraisal of cognitive and behavioral factors leading to the maintenance and exacerbation of pain (Turk, 2014). In addition, a recently completed qualitative study of case-level files found that when psychologists' adherence with the Clinical Framework was high in the treatment of musculoskeletal injuries (with a secondary psychological injury), lower claims costs and greater positive functional outcomes for injured people were observed (Haider, Dunstan, & Bhullar, 2018). However, this study also found that psychologists' use of these biopsychosocial intervention guidelines was suboptimal.…”
Section: Introductionmentioning
confidence: 99%